Uma investigação do desempenho do indicador PPI (poverty probability index) na aferição dos níveis de pobreza estaduais, suas diferenças e evolução - Arruda, Francisco Alexandre Correia (2023)
The objective of this work is to investigate the performance of the Poverty Probability Index (PPI) in measuring state poverty levels, their differences, and evolution. The indicator was created by economist Mark Shreiner, who used the PPI methodology for various countries. For comparison purposes and to define poverty percentages, two extreme poverty lines were used. The first is the extreme poverty line used in the Brazilian program Auxilio Brasil, which is 105 reais per person per month. The second is the extreme poverty line defined by the World Bank of 1.90 dollars per day for each individual, which is around 256 reais per month. The results indicate that there has been a decrease in the percentage of households in extreme poverty in Brazil from 2001 to 2019. However, there are still states with high percentages, such as Maranhão, Alagoas, Piauí, Pernambuco, and Ceará. When comparing the estimated PPI, it was noted that on average, it is adequate for evaluating poverty in the country as a whole with good model fit, and when comparing states, the difference in some cases is small. In addition, it is observed that even when using the LASSO (Least Absolute Shrinkage and Selection Operator) technique for cross-terms, there is not much variation in the results. Therefore, it is noted that the PPI can be used as an instrument for monitoring public policies.